Shadowgraphy of pulsed CO laser ablation of polymers - SIEW, W; TOU, T; WONG, K (2005)
Heavy plume expansions in air, helium and argon produced by pulsed CO2 laser ablations of poly(methyl methacrylate) (PMMA) and polyimide (PI) were imaged by shadowgraphy. The PMMA was melted at 1-2 mm depth beneath the surface followed by an outward expulsion of heavy plumes. A shock front was formed which detached from the first plume after several microseconds. A second, mushroom-shaped plume and a narrow ejection were also observed. In contrast, the mushroorn-shaped plume structure was absent in PI ablation, but it was in the form of a single blob, which collapsed back to the target. (c) 2005 Elsevier B.V. All rights reserved.